Implementasi Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Pemecahan Masalah dan Komunikasi Ilmiah Siswa SMA (UPEJ Unnes Physics Education Journal, 2018)
This study aim to determine the effect of guided inquiry learning model toward ability of problem solving and scientific communication of high school students on dinamic fluid materials, and to know the student’s response toward the implementation of guided inquiry learning model. The research design is use quasi experimental and the type is nonequivalent control group design. The data of this research are collected by test, observation, and questionnaire. The result showed that the implementation of guided inquiry learning model positively influence the problem solving and scientific communication ability of high school students. The influence of the implementation of guided inquiry learning model to the problem solving ability of students is 62,74%, while the influence of the implementation of guided inquiry learning model to the student’s scientific communication ability of 86,73%. The student’s response toward the implementation of the guided inquiry learning model is very good that is 81,15.